Economic Linkage Between Rubber Plantation and Other Sectors In Indonesia - Ana Fauziyatun Nisa; Abdil Fadhil Ridho (SEAS (Sustainable Environment Agricultural Science), 2024)
Rubber plantation as a part of the agricultural sector is one of the important sectors contributing to national GDP. This study aims to observe the economic linkage between rubber plantation and other sector in Indonesia by using input-output analysis approach. The result shows that the value of the backward and forward linkage coefficient of variation of the rubber plantation is respectively 0,80 and 1,54. The number of backward linkage coefficient of variation which is less than one indicates that backward linkage is low, while the number of forward linkage coefficient of variation which is more than one shows forward linkage of rubber plantation in the national economy is high. This condition describes the rubber plantation including as the forward orientation sector in the economy of Indonesia.